Invited review: Improved control of Johne's disease in dairy cattle through advancements in diagnostics, testing, and management of young stock - Larissa Martins; Karin Orsel; Razieh Eshraghisamani; Jose Miguel Hernández-Agudelo; A. Caroline Pereira; Waseem Shaukat; Ad P. Koets; John P. Bannantine; Caroline Ritter; David F. Kelton; Richard J. Whittington; Maarten F. Weber; et al. (Journal of Dairy Science)
ABSTRACT: Johne's disease (JD; paratuberculosis) control programs have been regionally implemented across the globe, but few have successfully eradicated the pathogen (Mycobacterium avium ssp. paratuberculosis; MAP) causing this disease. The limited success may partly be attributed to excluding young stock (calves and replacement heifers or bulls) from testing strategies aimed at identifying MAP-infected cattle. Young stock can shed MAP in feces and can have detectable MAP-specific antibodies in blood, as confirmed in experimentally and naturally infected cattle. Furthermore, MAP transmission causes new infections in young stock. Calves and heifers are often included in JD management strategies on dairy farms but excluded from conventional diagnostic tests due to a presumed lag between infection and detection of MAP shedding and MAP-specific serum antibodies. We summarize evidence of MAP shedding early in the course of infection and discuss promising diagnostics, testing and management strategies to support inclusion of young stock in JD control programs. Improvements in fecal PCR, interferon-gamma release assay (IGRA), and ELISA enable earlier detection of MAP and specific early immune responses. Studies on IGRA and ELISA have focused on evaluation of new antigens and optimal age of testing. New diagnostics have been developed, including phage-based tests to detect viable MAP, as well as gene expression patterns and metabolomics to detect MAP-infected young stock. In addition, refinements in testing and management of calves and heifers may enable reductions in MAP prevalence. We provide recommendations for dairy farmers, researchers, veterinarians, and other stakeholders that may improve JD control programs with an objective to control and potentially eradicate JD. Additionally, we have identified the most pressing gaps in knowledge that currently hamper inclusion of young stock in JD prevention and control programs. In summary, transmission among young stock may cause new MAP infections, and appropriate use of new diagnostic tests, testing and management strategies for young stock may improve the efficacy of JD control programs.